Pola Asuh Pengetahuan Pemberian Makan dengan Status Gizi Balita - Indra Domil; Zulfiah Nurhidayah Tangio; Fitri Yani Arbie; M. Anas Anasiru; Rahma Labatjo; Novian Swasono Hadi (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Stunting is a nutritional problem that can reduce the quality of life of children later. There are several factors associated with stunting, including maternal knowledge. This study aims to determine the relationship between the knowledge of child feeding parenting styles and stunting incidence in Ilotidea Village, Tilango District, Gorontalo District. The research method used a cross-sectional study. The nutritional status was obtained by measuring the height/length of the toddler's body using a microtoise and measuring body length. Meanwhile, the age can be obtained through birth certificates or family cards. The two data were then categorized by using the index of height or body length according to age using the WHO Antro 2005 classification. Data regarding knowledge of feeding parenting styles for toddlers was obtained using a questionnaire. Statistical analysis used the chi-square test with a significance level of 0.05 and 95% CI. A sample of 33 toddlers was taken using random sampling. The results showed that the knowledge of child feeding parenting affects the incidence of stunting (p-value = 0.006). Conclusions about the knowledge of child feeding contribute to feeding practice. Therefore, efforts are needed to increase access to information regarding proper feeding for toddlers.